(untitled) (Journal of Misan Researches, 2025)
The research seeks to reveal the effectiveness of a proposed strategy according to (Seigler’s) theory in developing the comprehension of biological concepts and scientific identity among students of the College of Basic Education. The research was conducted on a sample of (80) male and female students divided into two experimental groups of (39) male and female students and the other control group of (41) male and female students. In light of the nature of the research, it was possible to determine the experimental design of the research by designing the experimental and control group with pre- and post-measurements. The two research tools were prepared: the first is a test of comprehension of biological concepts consisting of (40) multiple-choice paragraphs after analyzing the biological concepts in the academic content of the general biology subject, which included (10) concepts with four levels for each concept, namely (clarification, interpretation, application, and perspective-taking). The second tool is the scientific identity scale consisting of five dimensions. The results indicated the effectiveness of the proposed strategy according to (Seigler’s) theory in developing the comprehension of biological concepts and scientific identity. The researchers recommended the need to focus on teaching concepts Understanding it accurately; as it constitutes the cornerstone of the cognitive structure of learners, in addition to taking care of the aspects that touch on emotional, psychological and personal issues due to their great impact on their academic performance.